Sooting characteristics of polyoxymethylene dimethyl ether blends with diesel in a diffusion flame. (15th July 2018) - Tan, Yong Ren; Botero, Maria L.; Sheng, Yuan; Dreyer, Jochen A.H.; Xu, Rong; Yang, Wenming; Kraft, Markus
Graphical abstract: Highlights: Smoke points of diesel/ PODE n and other oxygenates were measured in a diffusion flame. Sooting propensity of all the oxygenated blends exhibited similar results Oxygen content has limited impact compared to dilution effect for soot suppression 'Active' soot suppression species can explain the sooting tendency of the fuels Abstract: In this paper, we investigate the sooting propensity of PODE n /diesel blends. The sooting characteristics of PODE n /diesel blends are determined using a standard ASTMD1322 smoke point lamp. The performance of PODE n with different chain length (addition of –CH2 O– units) is benchmarked against other oxygenated soot suppression additives, including esters (methyl butyrate), carbonates (dimethyl carbonate) and alcohols ( n -butanol). Soot reduction induced by the dilution of the aromatic fraction in the diesel fuel was found to have the biggest impact, followed by soot reduction by decreasing the hydrocarbon chain length and to a lesser extent increasing the oxygen content. The reason for the limited influence of oxygen content on soot suppression was further explored by examining the possible decomposition pathways and products of the different additives.